Substrate binding site of proteases from bacillus lehensis G1 by molecular docking / Noorulaini Sulaiman, Nor Muhammad Mahadi and Nur Zazarina Ramly - Sulaiman, Noorulaini; Mahadi, Nor Muhammad; Ramly, Nur Zazarina (Universiti Teknologi MARA, Negeri Sembilan, 2017)
Proteases are abundantly found in all living organisms that are essential to life. Microbial proteases possess a commercial value with various applications in industries. Some of the biotechnological applications are involved detergents, leather, food, pharmaceutical and bioremediation processes. The aim of the study is to analyses the binding cavities in protease, BleG1_1979, from Bacillus lehensis G1, in order to examine the interaction site of protease with other molecules. Protein encoding for BleG1_1979 is 19.2 kDa in size, with a predicted pI value of 5.35 and 42% identity with intracellular protease from Thermococcus onnurineus NA1 from PDB database. Molecular docking was run using Hex v8.0.0. Four substrates were docked to BleG1_1979 pocket cavities, and casein exhibited highest binding affinity as compared to collagen, gelatin and keratin. This has suggested that BleG1_1979 could rapidly hydrolyzed casein and B. lehensis G1 did not contain keratolytic activity. Docking results have provided a basis for further understanding the molecular mechanism of substrates preference for B. lehensis G1 protease. Such knowledge could be explored to expand the usefulness of microbial protease for industrial application.